ICT Use, Innovation, and Productivity Evidence from Sub-Saharan Africa - Cirera, Xavier (The World Bank, 2016)
This paper examines empirically the links between adoption of information and communications technology (ICT), defined as usage by firms, innovation, and productivity using firm-level data for a sample of six Sub-Saharan African countries: the Democratic Republic of Congo (DRC), Ghana, Kenya, Tanzania, Uganda, and Zambia. Although adoption of information and communications technology in these countries is still lagging behind OECD countries, there is significant heterogeneity on adoption rates across the countries. Kenya has the largest adoption rate of computer, software, and Internet usage. The Democratic Republic of Congo and Tanzania experience lower adoption rates. The degree of internationalization of the firm, use of technology, and extent of competition are important factors explaining firm-level use of ICT. The results of the estimates suggest that ICT use is an important and robust enabler of product, process, and organization innovation across all six countries. However, the final impact on productivity depends on the degree of novelty of the innovation introduced by the firm